The dependence of Germany on Russian gas: analysis and prospects in the context of the current Ukrainian crisis (Comillas Journal of International Relations, 2015)
Germany and Russia share a strong economic interdependence, Germany being presently the largest importer of Russian gas. At the time of writing, the on-going conflict between Ukraine and Russia, compounded with economic sanctions imposed on Russia by the European Union, has raised concerns about Russia as a reliable gas supplier. This article analyses Germany’s dependence on Russian gas within the present economic and political contexts and assesses a) the most plausible course of action of German energy policy, taking into account Germany’s current role as a gas transit country; and b) the impact of the present context on the shaping of Germany’s foreign policy towards Russia. It is concluded that energy policy measures will not enable drastic reductions in Germany’s dependence on Russian gas in the short term and, moreover, that no abrupt change of direction in German foreign policy towards Russia is to be expected.
Keywords: Germany’s natural gas dependence; German-Russian economic interdependence; German energy policy; Germany’s Russian policy; Ukrainian crisis